Community Service Group on Seagrass Ecosystem Management in the coastal Area of Laikang Village, Takalar Regency - hamsiah Hamsiah; Asmidar asmidar; Kasmawati Kasmawati; Damis, Damis (Universitas Muhammadiyah Sidenreng Rappang, 2026)
Seagrass ecosystems play a vital role in both the ecology and economy of coastal regions. Ecologically, seagrass beds serve as nursery grounds, spawning grounds, and feeding grounds for various aquatic organisms, particularly fish. However, the water conditions in Puntundo Village have suffered environmental degradation due to damage to the seagrass ecosystem and the community’s limited knowledge of seagrass rehabilitation techniques. This Community Service (PkM) activity aims to enhance the community’s understanding and skills in rehabilitating seagrass ecosystems using the plug and bamboo frame method in the coastal area of Laikang Village, Takalar Regency. The methods employed include outreach, training on seagrass planting media preparation, and a participatory approach involving the community from the preparation stage through to the implementation of the activity. The training was conducted on a community-based approach, adhering to international standards for seagrass rehabilitation through transplantation techniques. The results of the activity indicate that the partner groups have successfully carried out seagrass rehabilitation using the plug and bamboo frame methods. Monitoring revealed that seagrass on the bamboo frames partially dried out due to sun exposure during the lowest low tide, whereas the plug method provided better protection for the plants, resulting in lower levels of desiccation.